Pengaruh Pemahaman Peraturan Pemerintah Nomor 55 Tahun 2022, Kesadaran Pajak dan Sanksi Pajak pada Kepatuhan Wajib Pajak Badan (Studi Kasus pada Perusahaan Industri di Kota Denpasar) - Sopiayanti, Ni Nyoman; Damayanthi, I Gst Ayu Eka (Universitas Batanghari Jambi, 2025)
This study aims to analyze the effect of Government Regulation of the Republic of Indonesia Number 55 of 2022 concerning Adjustments to Regulations in the Field of Income Tax, tax awareness, and tax sanctions on taxpayer compliance in industrial companies in Denpasar City. The number of samples based on the criteria in this study was 159 companies with a saturated sample method. The data analysis technique was carried out using the partial least square (PLS) method. The results of this study indicate that understanding of Government Regulation of the Republic of Indonesia Number 55 of 2022, tax awareness and tax sanctions have a positive effect on taxpayer compliance in industrial companies in Denpasar City. The results of this study support the theory of planned behavior and compliance theory where individual behavior has an influence on taxpayer compliance in Industrial Companies in Denpasar City